Thymoma. Presentation of a case. - Yandy Rodríguez Acosta; Reinaldo Jiménez Prendes; Nancy Capin Sarría (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
The case of a 31 years-old patient is presented, assisted in the University Hospital "Dr. Gustavo Aldereguía Lima" of Cienfuegos. This patient presented chest pain in its back right region, caused by a tumour in the anterior mediastinum, being carried out tymectomy by median sternotomy of Duval and Barostty. The hystopathological results showed lymphoepithelial thymoma stage II (invasive) with microscopic invasion of the capsule. The postoperative evolution was satisfactory with further ontological follow up.